Conservation status of upper-mesophotic octocoral habitats at Sporades Archipelago (Aegean Sea). (May 2023) - Chimienti, Giovanni; Maiorca, Michela; Digenis, Markos; Poursanidis, Dimitris
Abstract: Octocoral forests created by the yellow sea fan Eunicella cavolini and the red sea fan Paramuricea clavata were studied at the National Marine Park of Alonissos Northern Sporades (Aegean Sea, Greece), between 30 and 45 m depth, in order to assess their conservation status and the occurrence of both natural and anthropogenic stressors. The area was characterized by rich and dense coral forests, with densities up to 55.2 colonies m −2 for E. cavolini and 28.0 colonies m −2 for P. clavata . The coral population showed signs of stress, although mortality was low. A combination of stressors linked to global warming and fishing impacts, including macroalgal epibiosis, tip necrosis, increasing coral feeders, and abandoned fishing gears, could impair the status of these habitats in the near future. Although the effects of climate change are global, local conservation actions may reduce direct anthropogenic impacts and enhance habitats' resilience. Highlights: Sporades Archipelago is characterized by extensive and rich gorgonian forests. Forests of Eunicella cavolini and Paramuricea clavata show a high density. Corals' population structure, necrosis and epibiosis indicate a stressed condition. Increased abundance of thermophilic species suggests a thermal stress. Abandoned fishing gears are a further stressor.